Digital Games Cause to Brain (Global Journal of Human-Social Science, 2015)
This article discusses the ways in which digital games affect the behaviours of teenagers by promoting aggression Also highlighted is what the field of neuroscience can tell us about the implications of using digital games particularly with respect to their effects on teenagers brains and consequently on their behaviours In addition this paper demonstrates the importance of conducting research on the ways in which the use of digital games affect teenagers behaviour values and mental health and stresses the need to find ways in which to ensure the safe use of digital games and other new entertainment media
Keywords: digital games; violent games; aggressive behaviour; general aggregation model; psychological effects; teenage brain